Reliable and enhanced cooperative cross‐layer medium access control scheme for vehicular communication. Issue 4 (1st July 2018) - Eze, Elias; Zhang, Sijing; Liu, Enjie; Eze, Joy; Muhammad, Shehu
Abstract : In an unreliable cluster‐based, broadcast vehicular network setting, the authors investigate the transmission reliability and throughput performance of random network coding (RNC) as a function of the percentage of packet generation rate and transmit power‐to‐noise ratio. In this study, a novel scheme called reliable and efficient cooperative cross‐layer medium access control (RECMAC) is proposed. The proposed scheme consists of a source vehicle broadcasting packets to a set of receivers (i.e. one‐to‐many) over independent broadcast erasure channels. The source vehicle performs RNC on N packets and broadcasts the encoded message to a set of receivers. In each hop, several vehicles form a cluster and cooperatively transmit the encoded or re‐encoded packet. The combination of the RNC, cluster based, and cooperative communications enables RECMAC to optimally minimise data redundancy, which means less overhead, and improve reliability as opposed to coding‐based solutions. Theoretical analyses and simulation results show that under the same conditions RECMAC scheme can achieve improved performance in terms of transmission reliability and throughput.